2017
DOI: 10.1002/ajmg.a.38236
|View full text |Cite
|
Sign up to set email alerts
|

PLXNA1 developmental encephalopathy with syndromic features: A case report and review of the literature

Abstract: Developmental encephalopathies constitute a broad and genetically heterogeneous spectrum of disorders associated with global developmental delay, intellectual disability, frequent epilepsy, and other neurofunctional abnormalities. Here, we report a male presenting with infantile onset epilepsy and syndromic features resembling Dubowitz syndrome identified to have a de novo PLXNA1 variant by whole exome sequencing. This constitutes the second report of PLXNA1 sequence variation associated with early onset epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…However, this concept does not implicate the action of the Plexin-A1 co-receptor NRP1 and other protein-protein-interactions of the receptor. Furthermore, two of the previously published monoallelic de novo missense variants reside in extracellular domains of Plexin-A1 16 , 17 analogous to the here reported de novo missense variant in patient F:II-1. Finally, we report one de novo LoF variant in a neonate with severe neonatal hypotonia (L:II-3), which resides also in the extracellular domains of Plexin-A1.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, this concept does not implicate the action of the Plexin-A1 co-receptor NRP1 and other protein-protein-interactions of the receptor. Furthermore, two of the previously published monoallelic de novo missense variants reside in extracellular domains of Plexin-A1 16 , 17 analogous to the here reported de novo missense variant in patient F:II-1. Finally, we report one de novo LoF variant in a neonate with severe neonatal hypotonia (L:II-3), which resides also in the extracellular domains of Plexin-A1.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, the patient reported by Park et al showed prominence of ventricles. 16 plxna1a SB MO morphants showed hypoplasia of forebrain, midbrain, and hindbrain obtained in the transgenic reporter fish Tg ( -3.1ngn1:GFP ) ( Figure 4J ). Accordingly, six of our 10 patients presented with structural cerebral anomalies (C:II-2, D:II-1, D:II-2, E:II-1, G:II-1, H:II-1) ( Table 1 , Figure 4G,H ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…During embryogenesis, Plexin‐A joins with neuropilin to form a receptor for a group of chemorepellants called semaphorins that are important in axon guidance 1 . Due to its important role in axonal guidance and cell migration in the developing nervous system, pathogenic variants in PLXNA1 have been reported in individuals with developmental encephalopathy, seizures, dysmorphic features, and midline anomalies 2‐5 …”
mentioning
confidence: 99%
“…PLXNA1 is a transmembrane receptor for semaphorins, a large family of proteins that act as axonal guidance cues during nervous system development. Pathogenic variants in PLXNA1 were originally reported in individuals with neurological disorders such as epileptic encephalopathies, epilepsy, and neurodevelopmental syndrome, mainly comprising developmental delay and eye anomalies [12, 13]. Recently, a heterozygous nonsense PLXNA1 variant p.Glu1121Ter was identified as the candidate disease cause for a 38‐year‐old patient with developmental delay and parkinsonism [5], suggesting a potential role of PLXNA1 in parkinsonism.…”
Section: Discussionmentioning
confidence: 99%